Smart food for better health and nutrition – a promising concept - Garg, Aastha; Joshi, Kirti; Raghav, Pramod K (Journal of Postharvest Technology, 2022)
Smart food can be defined as foods that benefit us by providing sustainability in three ways by being good for our health, good for environment and favoring farmers’ livelihood. An initiative started by ICRISAT (International Crops Research Institute for the Semi-Arid Tropics) with an aim of increasing the staples from just big three crops and including millets and legumes in place due to the immense health benefits offered by them. Following 16 crops are included under the criteria: Pearl millet, Sorghum, Finger millet, Proso millet, Barnyard millet, Browntop millet, Foxtail millet, Little millet, Kodo millet, Teff, Fonio, Job’s Tear, Chickpea, Pigeon pea, Ground nuts and Green gram. Each of the mentioned crops is nutritionally rich and leads to improvement of overall health and nutritional status of people. Out of which pearl millet is one of most promising millet cultivated in Rajasthan, India that offers high nutritional and health benefits in addition of being staple growing crop of the region. These crops can be easily included in the daily meals due to their easy incorporation into daily recipes.